A pilot study evaluating the effect of mannitol and hypertonic saline solution in the treatment of increased intracranial pressure in 2 cats and 1 dog naturally affected by traumatic brain injury. Issue 5 (26th August 2019) - Ballocco, Isabella; Evangelisti, Maria Antonietta; Deiana, Roberta; Cubeddu, Francesca; Pinna Parpaglia, Maria Luisa; Serra, Giovanna; Carta, Giovanni; Manunta, Maria Lucia
Abstract: Objective: To evaluate the effects of iso‐osmolar doses of 18% mannitol and 3% sodium chloride (NaCl) solutions in decreasing intracranial pressure (ICP) in animals with severe traumatic brain injury (TBI). Design: Prospective uncontrolled interventional study. Setting: Veterinary university teaching hospital. Animals: Two cats and 1 dog with TBI with a modified Glasgow Coma Scale score ≤8 after hemodynamic stabilization, and with brain magnetic resonance imaging changes suggestive of intracranial hypertension. Interventions: Animals were surgically instrumented for direct ICP measurement, then randomly treated with iso‐osmolar doses of 18% mannitol or 3% NaCl. Direct ICP and cerebral perfusion pressure (CPP) were recorded both before treatment and for 120 minutes following drug administration. Measurements and Main Results: Direct ICP and CPP were recorded both before treatment and at 5 additional time points following administration over the subsequent 120 minutes. Case 1 received 3% NaCl without any response to therapy; refractory posttraumatic hypertension was suspected. Case 2 was treated with 3% NaCl; ICP decreased by 40.7% and CPP increased by 15%; however, these effects were transient. Case 3 received 18% mannitol, and ICP decreased by 19% and CPP increased to normal. However, there was a rebound increase in ICP that was higher than pretreatment values, and CPP decreased slightly before it gradually increased to normal values towards the end of the study. Conclusions: Both mannitol and hypertonic saline decrease ICP and improve CPP, but the effect observed in this pilot study suggests that there might be differences in the duration of these effects. Appropriately designed studies in a larger and homogeneous population are warranted to further investigate these findings.